2023
DOI: 10.1021/acs.analchem.2c04843
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Geometry of the Carbon Nanofiber Electrodes Provides Control over Dopamine Sensor Performance

Abstract: One of the major challenges for in vivo electrochemical measurements of dopamine (DA) is to achieve selectivity in the presence of interferents, such as ascorbic acid (AA) and uric acid (UA). Complicated multimaterial structures and ill-defined pretreatments have been frequently utilized to enhance selectivity. The lack of control over the realized structures has prevented establishing associations between the achieved selectivity and the electrode structure. Owing to their easily tailorable structure, carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…We used DA and AA as analytes as we have studied the electrochemical activity of these biomolecules on carbon nanofibers grown on similar systems containing these adhesion layers in previous reports. 8,16 Both Cr/Si and Ti/Si before annealing could not detect either ascorbic acid or dopamine on their surface. After annealing, Ti/Si does not show any electrochemical activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used DA and AA as analytes as we have studied the electrochemical activity of these biomolecules on carbon nanofibers grown on similar systems containing these adhesion layers in previous reports. 8,16 Both Cr/Si and Ti/Si before annealing could not detect either ascorbic acid or dopamine on their surface. After annealing, Ti/Si does not show any electrochemical activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic voltammograms for AA oxidation on CrNi and TiNi electrodes exhibited a peak around 465–500 mV, indicating the oxidation reaction from ascorbic acid to dehydroascorbic acid. The oxidation potential of AA is fairly anodically shifted than the observed oxidation peak position for CNFs . Similarly in the case of DA, a small peak at approximately 350 mV suggests a limited contribution from the CrNi and TiNi surfaces to the oxidation of DA to DAQ, with no corresponding reduction peak (Figure A,D).…”
Section: Resultsmentioning
confidence: 71%
“…The uncompensated resistance (Ru) was determined for each electrode in phosphate-buffered saline (PBS). The composition of PBS solution is given elsewhere . To evaluate the electrochemical activity of the electrodes in the PBS solution, dopamine hydrochloride (Sigma-Aldrich) and ascorbic acid (AA) from Merck were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we have shown that (1) the microstructure of CNFs is strongly affected by the adhesive layer metallurgy, and (2) these structural changes have observable effects on the surface chemistry. Finally, this work provides a foundation for tailoring the features of CNFs for electroanalytical chemistry, which we have described in a separate work [42].…”
Section: Discussionmentioning
confidence: 99%